O lúdico na escola: um instrumento indispensável no processo ensino aprendizagem - SILVA, Maria do Carmo Fernandes da (2023)
This work aimed to observe students who, through play, develop important skills such as socialization, creativity, memorization, imagination and maturity, demonstrating the importance of working with play in teaching Portuguese in the 1st year of elementary school. at Escola Conego Francisco da Silva Cravo which is located in the municipality of Barcarena, Pará. The work is supported by expressive theoretical references such as Rangel (2008), Santos (1997), Lopes (2006), among others. The proposal presented allows us to state that the teacher is a key player, through whom children will find in schools the tools and methods of systematizing knowledge, progress insofar as they trigger challenging situations, inserting play as an indispensable tool for children. really appreciate the will to talk, to read, to write, to exchange their experiences, ideas and points of view, to share interests and needs, aspirations and feelings. The research methodology presents the procedures that will discuss the selection of informants and data analysis, involving (01) a director, (01) deputy director, (01) pedagogical coordinator, (02) teachers, (35) students, using the data collection technique such as: interview, questionnaire, observation, essential support for the theoretical deepening of the research.